Elite pribumi Bengkulu : perspektif sejarah abad ke-19 - Setiyanto, Agus, 1958- (Jakarta : Balai Pustaka, 2001)
History of the elites in politics and government of Bengkulu Province in the 19th century
Revision of the author's thesis, Universitas Gadjah Mada, 1996
Includes bibliographical references (p. 303-317)
Keywords: Elite (Social sciences) -- Indonesia -- Bengkulu (Province) -- History; Bureaucracy -- Indonesia -- Bengkulu (Province) -- History; Bengkulu (Indonesia) -- Social life and customs; Indonesia -- Politics and government -- 1798-1942